Differences in Nutritional Value of Rice Crackers with the Addition of Three Types of Leaves (Moringa, Torbangun, and Katuk) - Nurifah, Churiyah; Rosida, Dedin Finatsiyatul; Munarko, Hadi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Rice crackers are a popular snack made from rice flour, typically characterized by a moisture content of less than 3%. The incorporation of moringa, torbangun, and katuk leaves in their formulation is based on their high iron content, which can help reduce iron deficiency. Additionally, xanthan gum is added to enhance the texture of the final product. This study aimed to evaluate the effects of different leaf types and xanthan gum concentrations on the nutritional properties of rice crackers. A factorial Completely Randomized Design (CRD) was employed, with two factors and two replications. Factor I was the type of leaf (moringa, torbangun, and katuk), while Factor II was the xanthan gum concentration (0.5%, 1%, and 1.5%). Data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level, and significant interactions were further examined using Duncan’s Multiple Range Test (DMRT) at 5%. The results indicated that the type of leaf and xanthan gum concentration had a significant effect (P<0.01) on moisture, ash, fat, protein, and carbohydrate content. The highest moisture (2.93%), ash (3.12%), and protein (1.29%) contents were observed in rice crackers containing moringa leaf and 1.5% xanthan gum. The highest fat content (6.10%) was found in moringa leaf rice crackers with 0.5% xanthan gum, while the highest carbohydrate content (82.55%) was recorded in torbangun leaf rice crackers with 1% xanthan gum. These findings highlight the potential of incorporating iron-rich leaves and xanthan gum to improve the nutritional quality and textural properties of rice crackers. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 3: Good Health and Well-Being SDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action